Comparison of Intraocular Pressure After Water Drinking Test in Primary Open Angle Glaucoma Patients Controlled with Latanoprost and Trabeculectomy - Emma Rusmayani; Widya Artini; Wresti Indriatmi (Majalah Oftalmologi Indonesia, 2021)
Purpose: To compare intraocular pressure (IOP) after water drinking test in primary open angle glaucoma patients controlled with latanoprost 0.005% and trabeculectomy.Methods: Observational study with cross-sectional design of 28 eyes with primary open angle glaucoma (POAG) patients. Subjects were divided into two groups, 14 patients controlled with trabeculectomy and 14 patients with latanoprost monotherapy. All subjects were under clinical therapy and had an intraocular pressure (IOP) equal or lower than 18 mm Hg, monitored during the follow up period. All subjects were submitted to the water drinking test. The results of the water drinking test, which were peak and fluctuation of IOP, were then compared between groups. Results: There were no significant difference between IOP peak between two groups (p=0.88). IOP fluctuation also showed no significant difference between groups (p=0.84). In both groups, baseline IOP strongly correlated with peak IOP in water drinking test with correlation coefficient r=0.96 (p<0.001) and r=0.71 (p=0.04), while baseline IOP in trabeculectomy group was strongly correlated with IOP fluctuation with correlation coefficient r=0.86 (p<0.001). Conclusions: Peak and fluctuation of IOP after water drinking test in primary open angle patients controlled with latanoprost and trabeculectomy showed no significant difference.